The Role of False Self-Presentation and Social Comparison in Excessive Social Media Use - Nor Fariza Mohd Nor; Nayab Iqbal; Azianura Hani Shaari (Behavioral Sciences)
Excessive social media use has become a growing concern due to its potential to affect self-perception, particularly through lowered self-esteem and a heightened fear of negative evaluation. With the increasing tendency for individuals to curate idealised online personas, understanding the psychological factors that drive this behaviour is critical. This study applies Self-Discrepancy Theory, Social Comparison Theory, and Gender Schema Theory to explain how self-perception, constant comparisons, and internalised gender norms drive online behaviours. A survey of 400 active social media users in Pakistan was conducted, and the data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). This study revealed that false self-presentation significantly heightened the fear of negative evaluation, which mediated its influence on excessive social media use. Social comparison, contrary to expectations, boosted self-esteem while also fuelling excessive use, as individuals sought validation online. Gender also appeared to play a moderating role, with women experiencing a stronger link between social comparison and self-esteem. However, gender did not moderate the relationship between false self-presentation and the fear of negative evaluation, suggesting similar psychological effects across genders. This study highlights that the fear of negative evaluation and social comparison-driven self-esteem are key psychological mechanisms behind excessive social media use, while gender plays a role in shaping the impact of social comparison but not false self-presentation. This study provides empirical evidence that excessive social media use is shaped by psychological factors, such as fear of negative evaluation and validation-seeking, driven by social comparison. Interventions aimed at reducing the emotional distress associated with excessive social media use should prioritise digital literacy programs that help users identify how false self-presentation and social comparison shape their fear of negative evaluation and validation-seeking behaviours, especially in appearance-driven online environments.